Gestão Sustentável: avaliação da responsabilidade socioambiental em meios de hospedagem no litoral norte da Paraíba - Cesar, Pedro Henrique; Durante, Daniel; Santos, Joel Silva dos; Moreira, Sueli Aparecida (Revista Brasileira de Ecoturismo (RBEcotur), 2018)
O litoral norte da Paraíba apresenta um contexto singular que inclui arquitetura barroca, presença indígena e o santuário do peixe boi (Trichechus manatus). A região contém o maior numero de unidades de conservação do estado da Paraíba. O aumento da visitação turística torna necessário o planejamento turístico sustentável da região. No contexto ecológico, a hotelaria deve prestar serviços com impacto ambiental reduzido para promover o desenvolvimento local sustentável. O presente estudo pretende observar a gestão da hotelaria do litoral norte da Paraíba sob o paradigma da sustentabilidade. Através de pesquisa qualitativa, os gestores responsáveis pelo serviço de hotelaria foram entrevistados. A gestão da hotelaria do litoral norte da Paraíba atua de modo inadequado às premissas do desenvolvimento sustentável. O contexto local demanda planejamento turismo ecológico para evitar a desestruturação da natureza e da cultura tradicional.Sustainable management: evaluation of socio-environmental responsibility in the lodging facilities of the northern coast of Paraíba (Brazil)ABSTRACTThe northern coast of Paraiba presents a singular context that includes Baroque architecture, indigenous presence and the sanctuary of Manatees (Trichechus manatus).The region contains the largest number of conservation units in the state of Paraiba. The increase in tourist visitation makes the region's sustainable tourist planning necessary. In the ecological context, the hospitality industry must provide services with reduced environmental impact to promote sustainable local development. This study aims to observe the management of the hospitality of the north coast of Paraiba under the sustainability paradigm. Through qualitative research the managers responsible for the hospitality service were interviewed. The management of the hospitality of the north coast of Paraiba acts inappropriately to the premises of sustainable development. The local context demands ecological tourism planning to avoid the destructuring of nature and traditional culture. KEYWORDS: Hospitality Industry; Sustainable Management; Ecological Tourism.